SWAP - Mavila Hinojoza, Daniel (2010)
The handling of market risk management can be done through derivative instruments for hedging purposes. The swap transaction is one of the financial instruments available to the financial manager and that is the subject of this article. Also application cases are appearing for the company mitigates the possibility of suffering losses due to unexpected and adverse movements in interest rates, exchange rates, stock prices and raw materials or commodities.